Hubungan antara Persepsi Interpersonal Relationship Siswa Terhadap Guru dengan Prestasi Belajar Siswa - Hayati Rahman, Ulfa; Duryati, Duryati (JFACE: Journal of Family, Adult, and Early Childhood Education, 2020)
Relationship Perceived Interpersonal Relationship Students And Teachers With Student Achievement. This study began based on the phenomenon of the low value of the National Exam achievement of Muhammadiyah High School students. The purpose of this study is to describe the relationship between perceptions of interpersonal relationships between students and teachers with the learning achievements of students of Padang Panjang Muhammadiyah High School. Research subjects numbered 86 people who were obtained through proportional stratified random sampling technique. Data collection uses a QTI scale determined from aspects of the model of interpersonal teacher behavior (MITB) by Wubbels and Levy (1993). Data is processed using the product moment correlation statistical technique. The results of the study with a rxy value of 0.473 with p = 0.000 (p <0.01) showed that there was a significant positive relationship between perceptions of students 'interpersonal relationships with teachers and students' learning achievements in Padang Panjang Muhammadiyah High School. Keyword: Interpersonal Relationship, QTI, Student Achivement